PENGARUH ONLINE CUSTOMER REVIEW, CUSTOMER RATING, DAN VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN GENERASI Z PADA TOKOPEDIA - Aida Faradilla Kamal, (2022)
Tokopedia is the most visited e-commerce platform in Indonesia. However, currently, there is a problem because Tokopedia is still below its competitors in purchasing decisions in generation Z. So the formulation of the problem in this study is whether customer reviews, customer ratings, and viral marketing affect purchasing decisions. This research aims to find out, prove, and analyze the influence of customer reviews, customer ratings, and viral marketing on purchasing decisions. The population in this study is generation Z consumers who have made purchases at Tokopedia in Jakarta. The sample used was 100 respondents, with quantitative data types and non-probability sampling (purposive sampling) methods. The analysis technique in this study used Partial Least Square (PLS) with SmartPLS 3.0 software. The results of this research show that the variables of customer reviews, customer rating, and viral marketing have a positive and significant influence on purchasing decisions. This study obtained the results that the customer review variable had the highest influence on the t-statistical test, which was 49.2%.